THE PECULIARITY OF MEDIEVAL MONUMENTS LOCATED IN SURKHANDARYA REGION (International journal of artificial intelligence, 2025)
this scientific article analyzes the architectural, cultural and historical significance of medieval historical monuments in Surkhandarya region. The geographical location and historical conditions of the region have fully integrated with its unique architectural heritage. The article covers ancient cities, cultural centers, mosques, mausoleums and other historical monuments in Surkhandarya. These monuments are not only studied as architectural monuments, but also their internal spiritual and religious nature. The article also examines the important role that Surkhandarya played in the fields of trade, culture and science in the Middle Ages, as well as the influence of the province on the connections between different peoples and cultures. Historical monuments of the Middle Ages today are of great importance not only for scientific research, but also in terms of cultural tourism and the preservation of historical heritage.